Application of QCM sensor device in some aqueous solutions / Z.A.Talib … [et al.] - Talib, Z.A.; B., Zuraidah; A., Kassirn; I.V, Grozescu (2004)
The quartz crystal microbalance (QCM) is well-established method for the measurement of small changes in mass, based on the relationship between changes in mass of material attached to the crystal and the oscillation frequency of the crystal. This device were set-up to present the practical approach to the development of instrument control software in the LabVIEW environment using the GPIB interface in order to investigate the influence of density and viscosity of some aqueous solution to the frequency response of the QCM and the results were correlated with the theory.